Denitrifying Bacteria Active in Woodchip Bioreactors at Low-Temperature Conditions - Jang, Jeonghwan; Anderson, Emily L.; Venterea, Rodney T.; Sadowsky, Michael J.; Rosen, Carl J.; Feyereisen, Gary W.; Ishii, Satoshi (Frontiers in Microbiology, 2019)
Woodchip bioreactor technology removes nitrate from agricultural subsurface drainage by using denitrifying microorganisms. Although woodchip bioreactors have demonstrated success in many field locations, low water temperature can significantly limit bioreactor efficiency and performance. To improve bioreactor performance, it is important to identify the microbes responsible for nitrate removal at low temperature conditions. Therefore, in this study, we identified and characterized denitrifiers active at low-temperature conditions by using culture-independent and -dependent approaches. By comparative 16S rRNA (gene) analysis and culture isolation technique, Pseudomonas spp., Polaromonas spp., and Cellulomonas spp. were identified as being important bacteria responsible for denitrification in woodchip bioreactor microcosms at relatively low temperature conditions (15°C). Genome analysis of Cellulomonas sp. strain WB94 confirmed the presence of nitrite reductase gene nirK. Transcription levels of this nirK were significantly higher in the denitrifying microcosms than in the non-denitrifying microcosms. Strain WB94 was also capable of degrading cellulose and other complex polysaccharides. Taken together, our results suggest that Cellulomonas sp. denitrifiers could degrade woodchips to provide carbon source and electron donors to themselves and other denitrifiers in woodchip bioreactors at low-temperature conditions. By inoculating these denitrifiers (i.e., bioaugmentation), it might be possible to increase the nitrate removal rate of woodchip bioreactors at low-temperature conditions.